(untitled) (International Journal of Engineering and Computer Science, 2014)
As ‘3D object picking in non immersive virtual world’ is an essential interaction technique in virtual environment, it is performed using a 3D mouse or an interactive glove to explore and interact with any of the objects. In this paper we focused the advantages of picking using bounding box and pick cube algorithm over picking using bounding sphere and pick sphere algorithm .The usefulness and effectiveness of the proposed evaluation measures are shown by reporting the performance evaluation of two algorithms. We then compare the application of both algorithms with related work to demonstrate that they are more suitable. These analytical studies provide distinct advantages in terms of ease of use and efficiency because they consider the tasks of object picking effective application-independent picking technique for various input devices. In this paper, cube and sphere are used to represent the intersection point of the ray coming from the user input and the object to be picked. By intersecting the objects in the scene with the ray with a pick cube at the intersection point, it is determined which one is picked. An object is selected when this pick cube intersects the object’s bounding box.